When full insurance may not be optimal: The case of restricted substitution - Johannes G. Jaspersen (Health Economics, 2022)
Even when heavily subsidized, a substantial portion of people choose to forgo purchasing health insurance coverage. In this note, I introduce an explanation for this phenomenon which does not assume choice errors, incorrect beliefs, differently priced uncompensated care, or information asymmetries. When individuals are incapable of freely trading off health and wealth and the initial allocation of goods is suboptimal from their perspective, the standard result of demand for actuarially fair insurance in a single good world does not generalize to the health insurance context. Thus, people might not purchase full health insurance coverage even if it is priced at actuarially fair levels. I argue that this situation is particularly likely to occur in the low-income population, and hence it is relevant for the achievement of universal health coverage.
Keywords: 330; health insurance; underinsurance